Coronary Wave Intensity Analysis as an Invasive and Vessel-Specific Index of Myocardial Viability. (20th December 2022) - Ryan, Matthew; De Silva, Kalpa; Morgan, Holly; O'Gallagher, Kevin; Demir, Ozan M.; Rahman, Haseeb; Ellis, Howard; Dancy, Luke; Sado, Daniel; Strange, Julian; Melikian, Narbeh; Marber, Michael; et al.
Abstract : Background: Coronary angiography and viability testing are the cornerstones of diagnosing and managing ischemic cardiomyopathy. At present, no single test serves both needs. Coronary wave intensity analysis interrogates both contractility and microvascular physiology of the subtended myocardium and therefore has the potential to fulfil the goal of completely assessing coronary physiology and myocardial viability in a single procedure. We hypothesized that coronary wave intensity analysis measured during coronary angiography would predict viability with a similar accuracy to late-gadolinium–enhanced cardiac magnetic resonance imaging. Methods: Patients with a left ventricular ejection fraction ≤40% and extensive coronary disease were enrolled. Coronary wave intensity analysis was assessed during cardiac catheterization at rest, during adenosine-induced hyperemia, and during low-dose dobutamine stress using a dual pressure-Doppler sensing coronary guidewire. Scar burden was assessed with cardiac magnetic resonance imaging. Regional left ventricular function was assessed at baseline and 6-month follow-up after optimization of medical-therapy±revascularization, using transthoracic echocardiography. The primary outcome was myocardial viability, determined by the retrospective observation of functional recovery. Results: Forty participants underwent baseline physiology, cardiac magnetic resonance imaging, and echocardiography, and 30 had echocardiography at 6 months; 21/42 territories were viable on follow-up echocardiography. Resting backward compression wave energy was significantly greater in viable than in nonviable territories (−5240±3772 versus −1873±1605 W m −2 s −1, P <0.001), and had comparable accuracy to cardiac magnetic resonance imaging for predicting viability (area under the curve 0.812 versus 0.757, P =0.649); a threshold of −2500 W m −2 s −1 had 86% sensitivity and 76% specificity. Conclusions: Backward compression wave energy has accuracy similar to that of late-gadolinium–enhanced cardiac magnetic resonance imaging in the prediction of viability. Coronary wave intensity analysis has the potential to streamline the management of ischemic cardiomyopathy, in a manner analogous to the effect of fractional flow reserve on the management of stable angina.